Innovations in buyouts: lessons from lived and learned experience - Weber, Anna; Marcell, Kristin; Osthues, Maggie; Hanson, Shameika; Hulet, Carri (Frontiers in Climate, 2025)
Across the United States, tens of thousands of people have sold their homes to the government to address risk from flooding or another natural hazard. After the sale, the structure is typically demolished and the land preserved as open space. This process, referred to as a home buyout, is the nation’s primary mechanism for relocation assistance in the aftermath of a disaster or in the face of recurring hazards, and the number of homes that have been purchased and demolished in the past is dwarfed by the number that is anticipated in the future. Community members, researchers, practitioners, and advocates have long observed challenges with government-funded home buyout programs in the United States. Often, home buyouts do not meet communities’ needs and can even create new problems. At the same time, demand for relocation support is growing in many areas, while current funding, programming, and expertise is insufficient to address the scale of the challenge. We need better buyouts that work for residents and local governments alike. To build a better buyout, we need to draw from the lived and learned experiences of both community members and practitioners. Between December 2021 and October 2022, the Natural Resources Defense Council (NRDC), in partnership with the Federal Emergency Management Agency (FEMA), CH Consulting, The Nature Conservancy (TNC), and the Climigration Network, convened conversations with buyout practitioners and buyout participants/residents of communities affected by buyouts. The participants spanned 14 states, from coastal to inland locations across the contiguous United States. This policy and practice review summarizes the recommendations generated through these workshop series, as well as the methods used to design and facilitate the sessions and subsequent work done to implement the recommendations and develop a community of practice for better buyouts.